Analisis Kemampuan Petugas Penyuluh Lapangan Keluarga Berencana (PLKB) Dalam Melaksanakan Program Kependudukan Keluarga Berencana dan Pembangunan Keluarga (KKBPK) di Kabupaten Tapanuli Utara Tahun 2018 - Irmauli Simanjuntak; Tarsyad Nugraha; Asyiah Simanjorang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Family Planning Program (KB) is one of the basic social programs that are very important for the progress of a nation. The National Family Planning Program has been inseparable from the role of Planning Field Planners (PLKB) officers. The success of the PLKB in carrying out their duties is supported by their ability in mastering the National Family Planning Program in the face of changing environmental conditions. Objectives; to determine the ability of PLKB officers and efforts to improve the capacity of the PLKB in implementing KKBPK programs in North Tapanuli Regency. Method; The research design used in this study is a combination of quantitative and qualitative methods (mixed method). The samples in this quantitative research is that all PLKB in North Tapanuli Regency are 26 PLKB people. The informants for the qualitative research were PLKB in Simangumban District, North Tapanuli Regency as the main informants and Head of Division, Head of Program Sub-Division and Planning of PPKBP3A Office, and the Village Head as triangulation informant. Data analysis used is univariate and bivariate analysis with chi square statistical test for quantitative research and data reduction stages, data display, and conclusionorverification. Results; that the p-value of the knowledge variable was 0.000 <0.05 and the p-value for the attitude variable was 0.003 <0.05. Conclusion; there is a relationship between knowledge and attitudes with the ability of the PLKB officers to implement the KKBPK program in North Tapanuli District in 2018